EDUCATION, TEACHERS IN RECENT TIMES. THREE RESEARCHES (2011)
The set of reflections here presented answer to the efforts did during the development of three Education researches, Pedagogy and its practices during the last half-century and early twenty-first century. Researches were undertaken from an interpretive phenomenological approach, allowing to provide witnesses and informants of the first source on the subject under study. The methods used were interviews, Life History, Oral History and Stories. The historical sense was achieved in the research invited to think once again the development of Education in the times to come.